Factors influencing students’ usage satisfaction toward university web portal: a pls-sem analysis - Syed Shah Alam,; Md Daud Ismail,; Mohd Helmi Ali,; Zaher Zain, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
The aim of this study is to empirically examine the factors affecting users’ satisfaction with university portals in Malaysia. This study tested seven hypotheses on factors affecting users’ satisfaction of university portal with empirical data from a sample of 318 students from Universiti Kebangsaan Malaysia. Data were collected through personal-administered questionnaire. Partial Least Square (PLS) analysis results revealed that system quality, information quality, service quality, user ability, and educational services were significantly influence users satisfaction. Information quality was found as the dominating factor in this research.